Benzoxazolinone detoxification by N-Glucosylation: The multi-compartment-network of Zea mays L. (2nd January 2016) - Schulz, Margot; Filary, Barbara; Kühn, Sabine; Colby, Thomas; Harzen, Anne; Schmidt, Jürgen; Sicker, Dieter; Hennig, Lothar; Hofmann, Diana; Disko, Ulrich; Anders, Nico
ABSTRACT: The major detoxification product in maize roots after 24 h benzoxazolin-2(3 H )-one (BOA) exposure was identified as glucoside carbamate resulting from rearrangement of BOA- N -glucoside, but the pathway of N -glucosylation, enzymes involved and the site of synthesis were previously unknown. Assaying whole cell proteins revealed the necessity of H2 O2 and Fe 2+ ions for glucoside carbamate production. Peroxidase produced BOA radicals are apparently formed within the extraplastic space of the young maize root. Radicals seem to be the preferred substrate for N -glucosylation, either by direct reaction with glucose or, more likely, the N -glucoside is released by glucanase/glucosidase catalyzed hydrolysis from cell wall components harboring fixed BOA. The processes are accompanied by alterations of cell wall polymers. Glucoside carbamate accumulation could be suppressed by the oxireductase inhibitor 2-bromo-4´-nitroacetophenone and by peroxidase inhibitor 2, 3-butanedione. Alternatively, activated BOA molecules with an open heterocycle may be produced by microorganisms (e.g., endophyte Fusarium verticillioides ) and channeled for enzymatic N -glucosylation. Experiments with transgenic Arabidopsis lines indicate a role of maize glucosyltransferase BX9 in BOA- N -glycosylation. Western blots with BX9 antibody demonstrate the presence of BX9 in the extraplastic space. Proteomic analyses verified a high BOA responsiveness of multiple peroxidases in the apoplast/cell wall. BOA incubations led to shifting, altered abundances and identities of the apoplast and cell wall located peroxidases, glucanases, glucosidases and glutathione transferases (GSTs). GSTs could function as glucoside carbamate transporters. The highly complex, compartment spanning and redox-regulated glucoside carbamate pathway seems to be mainly realized in Poaceae. In maize, carbamate production is independent from benzoxazinone synthesis.